Parental Involvement and Student Achievement: Could Technology Play A Role? - Hendley, Sheila (My University, 2001)
A study that included forty-eight participants from a small rural middle school was conducted to determine the effects of technology on parent and guardian attitudes about their involvement in school. Interventions included a school web page and weekly school newsletters. Pretest/Posttest research design was implemented and both interventions were evaluated. Three profiles - importance, productivity and comfort were studied. Posttest participants who utilized a school web page had more positive attitudes for all three profiles than either pretest participants or newsletter recipients. Changes in types of technology use as well as frequency of technology use were reported. Newsletter recipients reported improved attitudes about the productivity of their involvement but attitudes regarding comfort and importance declined.
Keywords: Technology; Attitudes; School web page